Semiotic systems, culture and early mathematical knowledge - Martí, Eduardo (2015)
In this introduction to the issue Semiotic tools in early mathematical knowledge, we offer a theoretical perspective that provides meaning to the different contributions. We begin by reviewing three perspectives bearing an important influence on the study of mathematical development in childhood (the Piagetian, the information processing and the neonativist perspectives). Next, we underscore the need for developmental studies in this domain to consider the semiotic component, and hence the socio-cultural component, in depth. The contributions that form this volume — a theoretical article, five papers and four short reports of empirical studies and a review of an instructional approach — illustrate different ways of including the semiotic component in the study of children’s mathematical knowledge.